Cystatin B deficiency results in sustained histone H3 tail cleavage in postnatal mouse brain mediated by increased chromatin-associated cathepsin L activity - Daura, Eduard; Tegelberg, Saara; Hakala, Paula; Lehesjoki, Anna-Elina; Joensuu, Tarja (Frontiers in Molecular Neuroscience, 2022)
Cystatin B (CSTB) is a cysteine cathepsin inhibitor whose bi-allelic loss-of-function mutations in human results in defects in brain development and in neurodegeneration. The physiological function of CSTB is largely unknown, and the mechanisms underlying the human brain diseases remain poorly understood. We previously showed that CSTB modulates the proteolysis of the N-terminal tail of histone H3 (H3cs1) during in vitro neurogenesis. Here we investigated the significance of this mechanism in postnatal mouse brain. Spatiotemporal analysis of H3cs1 intensity showed that while H3cs1 in wild-type mice was found at varying levels during the first postnatal month, it was virtually absent in adult brain. We further showed that the high level of H3cs1 coincides with chromatin association of de novo synthesised cathepsin L suggesting a role for nuclear cathepsin L in brain development and maturation. On the contrary, the brains of Cstb-/- mice showed sustained histone H3 proteolysis to adulthood with increased chromatin-associated cathepsin L activity, implying that CSTB regulates chromatin-associated cathepsin L activity in the postnatal mouse brain. As H3 tail proteolysis has been linked to cellular senescence in vitro, we explored the presence of several cellular senescence markers in the maturing Cstb-/- cerebellum, where we see increased levels of H3cs1. While several markers showed alterations in Cstb-/- mice, the results remained inconclusive regarding the association of deficient CSTB function with H3sc1-induced senescence. Together, we identify a molecular role for CSTB in brain with implications for brain development and disease.